Organizational Support for Green Hospital Initiatives in Indonesia: A Literature Review - Citra, Eka Widya; Triansyah, Ade; Astoro, Anjar Budi (Asian Journal of Healthcare Analytics, 2026)
Hospitals are resource-intensive institutions that contribute significantly to environmental burdens through energy use, water consumption, pharmaceuticals, chemicals, and waste production. In Indonesia, the green hospital concept has become increasingly important amid climate change and the pursuit of sustainable health governance. This study examines the organizational support that enables the implementation of green hospitals using a narrative literature review approach. The findings show that organizational support consists of leadership commitment, internal governance, employee engagement, budgeting, infrastructure, stakeholder collaboration, and environmental accountability systems. However, implementation remains constrained by policy fragmentation, limited funding, weak monitoring systems, and uneven organizational cultures. The study concludes that successful green hospital implementation depends not only on technology adoption but also on strong institutional capacity, integrated governance, and sustainable organizational support to achieve long-term environmental transformation in Indonesian hospitals.